2010
DOI: 10.1126/scisignal.2000502
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Group Proteins as Epigenetic Mediators of Neuroprotection in Ischemic Tolerance

Abstract: Exposing the brain to sublethal ischemia affects the response to a subsequent, otherwise injurious ischemia, resulting in transcriptional suppression and neuroprotection, a response called ischemic tolerance. Here, we show that the proteomic signature of the ischemic-tolerant brain is characterized by increased abundance of transcriptional repressors, particularly polycomb group (PcG) proteins. Knocking down PcG proteins precluded the induction of ischemic tolerance, whereas in an in vitro model, overexpressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 40 publications
2
100
3
Order By: Relevance
“…Recent studies indicate that polycomb repressive complex 2 (PRC2) is recruited to RE1-containing genes by REST via the noncoding RNA HOTAIR (54) and that PRC1 interacts with REST at RE1 sites (55). Moreover, polycomb proteins are activated and afford neuroprotection in the setting of ischemic preconditioning (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that polycomb repressive complex 2 (PRC2) is recruited to RE1-containing genes by REST via the noncoding RNA HOTAIR (54) and that PRC1 interacts with REST at RE1 sites (55). Moreover, polycomb proteins are activated and afford neuroprotection in the setting of ischemic preconditioning (56).…”
Section: Discussionmentioning
confidence: 99%
“…Differential demethylation and expression of Phc2 in injury may also be important. Several members of the polycomb family have been shown recently to be differentially upregulated and essential for the establishment of ischemic tolerance (Stapels et al, 2010). These included the polycomb repressive complex 1 (PRC1) member BMI1, which protects against chemical stress-induced cell death (Lee et al, 2008) and with which Phc2 has been shown to interact (Satijn et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…By favoring a more compact chromatin state, the PcG complex proteins appear to function as transcriptional repressors. Among the many genes that they repress, specific subtypes of potassium channels, such as KCNA5 and KCNB2, have been identified [20]. Repression of potassium channels not only leads to decreased consumption of adenosine triphosphate (ATP) (via decreased dependence and utilization of the Na + /K + ATPase to maintain potassium gradients), but can also lead to prolonged action potentials and increased conduction velocity.…”
Section: Introductionmentioning
confidence: 99%